Avaliação da aprendizagem no curso a distância de licenciatura em ciências biológicas da Universidade Estadual de Pernambuco - Rodrigues, Evanize Custódio (2010)
In contemporary society, distance education is expanding, especially in the offering of courses of initiatory professor training. By the side of possibilities, there is the need to critically reflect on the government decision to finance, and even to incite distance education, as a more economic way to achieve, within different time and space, the greatest quantity of the population, trying to fill the gaps of the Brazilian school education. The research was made in the Biology Bachelor Course offered by the Pernambuco University (UPE), in the context of the Presential Support Pole of the Paraiba State University, located in the city of Campina Grande. Along this study, we intend to analyze the evaluation practice and the instruments of valuation available in the virtual environment of learning (AVA), used by the former professors in the learning evaluation of the contents offered by the reference course. The relevance of the discussion is to reflect about the results of distance education in the initial of the professor training. To perceive the possibilities and limitations concerning the technological resources available at the educational process, especially to the evaluation practice, is primordial in order to comprehend the contents of learning that can be explored by the professors and which is the dialogical relation that is firmed between professor, preceptor and student, in favor of the learning development and an effective and meaningful education. The qualitative research had the symbolic interacionism as a methodological-theoretical approach. We gathered informations through institutional documents, documental records, questionnaires and semi-structured interviews. Treating and analyzing the data we used the content analysis method (Bardin, 1977). As a theoretical basis, we relied on authors such as Zabala (1998, 1999), Aretio (2002), Hoffmann (2003, 2005), Silva, M. (2003, 2006), Belloni (2006), Luckesi (2008), Silva, J. (2008), Vasconcelos (2008) and Domingos (2009). It was evident the need to reflect about the educational practice of the professors and preceptors responsible for the academic distance learning, concerning the evaluation of the learning contents in a autonomous and innovatory way, identifying its influence in the development of values which are considered vital to a complete professor upbringing. The evaluation in a mediator approach is necessary to the reality of an online classroom, because of its character to promote the improvement of the action of the one who is teaching and the one Who is learning in an interactive, collaborative and cooperative perspective, seeking a transformative praxis. Involved in this formation, the bachelors will be able to promote the development of capacities and skills necessary to the complete learning of theirs future students, certifying the education for life, which is a perspective that includes the knowing, the knowing how to do and how to be, a living being with sustainable relations with the others and with nature